Implementation of Teacher Competency in Utilizing it Technology for Indonesian Language Learning in 3t Madrasahs, Indragiri Hilir Regency - Lilik Mariyanizaitin; Tita Rosita; Elly Sukamana (Eduvest - Journal of Universal Studies, 2025)
This study explores the implementation of teacher competency in utilizing it technology for Indonesian language learning in 3T Madrasahs, Indragiri Hilir Regency by examining teachers’ competencies in utilizing information technology (IT) in Indonesian language learning within 3T (frontier, outermost, and underdeveloped) madrasahs in Indragiri Hilir Regency, Indonesia. Using a qualitative descriptive approach, the research involved classroom observations, in-depth interviews, and document analysis conducted at three madrasahs: MIS Islamiyah, MI Nurul Wathan, and MI Nurul Islam. Thematic analysis was applied to interpret the findings. The results indicate that although several teachers have begun integrating digital tools—such as laptops, projectors, or mobile devices—into their teaching, the overall use of technology remains basic and fragmented. Teachers primarily employ technology for visual presentations rather than for interactive learning. Key inhibiting factors include limited infrastructure, insufficient digital literacy, lack of institutional support, and geographical constraints. However, the study also reveals promising efforts made by teachers, including self-directed learning, informal peer collaboration, and adaptive use of simple technologies. These findings emphasize the need for systemic interventions, such as contextual digital training, provision of adequate infrastructure, and the establishment of a supportive school culture. Strengthening teacher capacity in IT usage is crucial not only for enhancing students’ engagement in Bahasa Indonesia learning but also for achieving equitable digital transformation in remote educational settings.